THE EFFECT OF INTEREST IN LEARNING, LEARNING READINESS AND FAMILY ENVIRONMENT ON LEARNING OUTCOMES - Syafira, Jihan Ayu; Zulaihati, Sri; Fauzi, Achmad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2020)
This study aims to determine the impact of learninginterest and family environment on learningdifficulties in accounting major of 41 state vocationalhigh school Jakarta. the population of this study was143 students. The sampling technique usesproportional random sampling to obtain a sample of105 students. Test requirements analysis is done, thedata are expressed in normal and linear distribution.Based on the analysis of the results of the studyconcluded that partially negative and not significant,and negative and significant effect (th1: -0,797; th2:-2,261 each < ttabel; 1,983). while simultaneouslyobtained Fcount (3,127) > Ftable (3,08) it can beconcluded that the variables of learning interest andfamily environment have a positive and significanteffect on learning difficulties by obtaining a multiplecorrelation coefficient of 0,465 and a coefficient ofdetermination of 46,5%.